Efficacy and safety of next-generation tick transcriptome-derived direct thrombin inhibitors - Cho Yeow Koh (Nature Portfolio, 2021)
Bleeding complications limits the use of effective antithrombotics therapeutics. Here, the authors developed next-generation direct thrombin inhibitors with low bleeding risks as safe peri-percutaneous coronary intervention anticoagulants when used in combination with antiplatelets.